(untitled) (Costa Rican Journal of Guidance & Counseling, 2025)
Objective: This article analyzes the professional development in Information and Communication Technologies (ICT) and the institutional support for guidance counselors in public schools in Costa Rica. Methodology: The methodology is quantitative, with an ex post facto, cross-sectional design and descriptive scope. The sample (n=328) comprises guidance professionals from the Ministry of Public Education, who completed a questionnaire. Results: The main findings reveal a critical perception of institutional support, particularly in aspects related to support for the exchange of technological experiences and attention to professional development needs. Although most of the sample reports receiving ICT training, the most valued modalities are those that promote collaborative learning and flexible access to resources. In contrast, less contextualized options, such as visits to other schools or short courses, are considered less effective. Conclusions: The importance of collaborative learning and access to updated resources for efficient training is highlighted. However, the lack of contextualization in some modalities and the limited institutional support hinder the integration of ICTs in guidance counseling. The design of practical and relevant programs is recommended, with greater involvement of the educational institutions in identifying the technological needs of the guidance counseling community.